2018 Typhoon Jebi post-event survey of coastal damage in the Kansai region, Japan. Issue 3 (3rd July 2019) - Mori, Nobuhito; Yasuda, Tomohiro; Arikawa, Taro; Kataoka, Tomoya; Nakajo, Sota; Suzuki, Kojiro; Yamanaka, Yusuke; Webb, Adrean
ABSTRACT: Typhoon Jebi in 2018 caused severe damage along areas of Osaka Bay, Japan. After the storm, a Japan Society of Civil Engineers (JSCE) coastal survey group surveyed the coastal impacts and recorded watermarks inside Osaka Bay and along the Pacific. The maximum storm tide recorded by a tide gauge was 3.29 m at the Osaka Tide Station, which is a historical high for Osaka Bay. Coastal flooding consisted of both storm surge and wave run-up in almost all locations, with flooding exceeding 5 m and 12 m in elevation from mean sea level in the inner parts of Osaka Bay and along the Pacific coast, respectively. Coastal damage was severe in areas located outside of coastal barriers, such as ports and harbors, while residential areas were mainly well protected and spared due to coastal protection systems. In addition, some inland flooding occurred in the Kobe-Ashiya regions due to the storm surge propagating up several small rivers. This survey report summarizes the findings of the post-event survey by JSCE and analyzes the relation between maximum water level and resulting damage.